The Efficacy of a Comprehensive Reminder System to Improve Health Behaviors and Blood Pressure Control in Hypertensive Ischemic Stroke Patients: A Randomized Controlled Trial. Issue 6 (November 2018) - Wan, Li-Hong; Zhang, Xiao-Pei; You, Li-Ming; Ruan, Heng-Fang; Chen, Shao-Xian
Abstract : Background and Objective: The health behaviors of hypertensive stroke patients in China are not satisfactory. In this study, we tested the effect of a Health Belief Model Comprehensive Reminder System on health behaviors and blood pressure control in hypertensive ischemic stroke patients after occurrence and hospital discharge. Methods: A randomized, parallel-group, assessor-blinded experimental design yielded participation of 174 hospitalized hypertensive ischemic stroke patients. The intervention consisted of face-to-face and telephone health belief education, a patient calendar handbook, and weekly automated short-message services. Data were collected at baseline and 3 months after discharge. Results: Three months after discharge, the intervention group showed statistically, significantly better health behaviors for physical activity, nutrition, low-salt diet, and medication adherence. The intervention group also had statistically, significantly decreased systolic blood pressure and increased blood pressure control rate. Smoking and alcohol use behaviors were not affected. Conclusion: At 3 months, use of the Comprehensive Reminder System based on the Health Belief Model, yielded improvement in most health behaviors and blood pressure control in hypertensive ischemic stroke patients. Continued implementation of this intervention protocol is warranted to determine the long-term effect. Smoking and alcohol use behaviors need to be targeted with a different intervention.